Graphene and related nanomaterials properties and applications - Bondavalli, Paolo (Amsterdam Elsevier, 2018)
Graphene and Related Nanomaterials: Properties and Applications outlines the physics and the applications of graphene-related materials, including graphene, graphene oxide and carbon nanotubes. The first chapter introduces the physics of graphene and related nanomaterials. The following sections deal with different applications spanning from gas sensors to non-volatile memories and supercapacitors. The book also covers spintronics for graphene. In each chapter, specific applications are explained in a detailed way. This book will appeal to materials scientists and engineers looking to understand more about the nature of graphene and how it is currently being used.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Graphene; Nanostructured materials; Electronic books